2021
DOI: 10.1186/s12879-021-05847-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences of blood cells, lymphocyte subsets and cytokines in COVID-19 patients with different clinical stages: a network meta-analysis

Abstract: Background Due to the rapid spread of coronavirus disease 2019 (COVID-19) worldwide, it is necessary to ascertain essential immune inflammatory parameters that describe the severity of the disease and provide guidance for treatment. We performed network meta-analyses to determine differences in blood cells, lymphocyte subsets, and cytokines in COVID-19 patients with different clinical stages. Methods Databases were systematically searched to May 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
7
19
1
Order By: Relevance
“…IL-10 on the other hand, by a direct effect on macrophages and T and B-cells has a major immune suppressive function and may counter-act to control this (hyper)inflammatory state caused by compound action of pro-inflammatory cytokines [ 12 , 13 ]. The association of these cytokines with COVID-19 severity has also been described in some previous studies [ 1 , 9 , 14 22 ]. In our study, these cytokines were also found to be high in the non-survivor group.…”
Section: Discussionsupporting
confidence: 77%
“…IL-10 on the other hand, by a direct effect on macrophages and T and B-cells has a major immune suppressive function and may counter-act to control this (hyper)inflammatory state caused by compound action of pro-inflammatory cytokines [ 12 , 13 ]. The association of these cytokines with COVID-19 severity has also been described in some previous studies [ 1 , 9 , 14 22 ]. In our study, these cytokines were also found to be high in the non-survivor group.…”
Section: Discussionsupporting
confidence: 77%
“…For orientation, we estimated the cellular composition of leucocytes based on DNA methylation profiles [11]. This analysis showed reduced fractions of lymphocyte subsets (CD4, CD8, NK and B-cells) and increased monocytes and granulocytes in COVID-19 patients, which is in line with previous and own measurements with flow cytometry (Supplementary Figure S2) [12].…”
Section: Resultssupporting
confidence: 86%
“…It has been reported that TNF alpha and interleukin 1-beta (IL-1beta) suppress serum EPCR level and simultaneously high sEPCR level was detected [ 30 , 31 ]. TNF alpha and IL-1beta are known to be among the major cytokines in the cytokine storm seen in COVID-19 course [ 32 ]. Steven et al [ 33 ] have suggested that considering the role of protein C system in inflammation and coagulation, APC may be involved in the treatment of disease based on the close relationship between inflammation and coagulation cascade in the course of COVID-19.…”
Section: Discussionmentioning
confidence: 99%